2002
DOI: 10.1111/j.1530-0277.2002.tb02450.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Activation of Alcohol‐Related Prenatal Memories: Impact on the First Suckling Response

Abstract: Prenatal experience with alcohol intoxication can result in chemosensory associative learning mediated by the drug's postabsorptive effects. This learning determines attachment patterns of newborns when they reexperience olfactory cues that had signaled onset of the state of acute alcohol intoxication when they were fetuses. Considered in view of previous experiments, the present results generate two alternative hypotheses relative to the affective component of the memory established in utero: (1) alcohol into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Pups prenatally exposed to paired experiences between cineole and the onset of alcohol intoxication, exhibited patterns of orofacial responses (mouthing) elicited by the CS that were significantly different from those found in infants that had originally experienced the CS and the US separated by a significant time delay (4 hr) or pups born to water treated females (Abate et al, 2000;Abate, Spear, & Molina, 2001). Using a similar experimental strategy it was also observed that neonates prenatally exposed to cineole associated with alcohol intoxication show heightened responsiveness to a nutritive surrogate nipple in the presence of the odor employed as a CS during late gestation (Abate, Varlinskaya, Cheslock, Spear, & Molina, 2002).…”
Section: Alcohol Responsiveness As a Function Of Fetal Experiences Wimentioning
confidence: 59%
“…Pups prenatally exposed to paired experiences between cineole and the onset of alcohol intoxication, exhibited patterns of orofacial responses (mouthing) elicited by the CS that were significantly different from those found in infants that had originally experienced the CS and the US separated by a significant time delay (4 hr) or pups born to water treated females (Abate et al, 2000;Abate, Spear, & Molina, 2001). Using a similar experimental strategy it was also observed that neonates prenatally exposed to cineole associated with alcohol intoxication show heightened responsiveness to a nutritive surrogate nipple in the presence of the odor employed as a CS during late gestation (Abate, Varlinskaya, Cheslock, Spear, & Molina, 2002).…”
Section: Alcohol Responsiveness As a Function Of Fetal Experiences Wimentioning
confidence: 59%
“…How the presence or absence of the prenatal CS modulated the structure of the first suckling response was addressed through tests with a surrogate nipple that delivered milk as a consequence of neonatal attachment (122)(123)(124). Neonates prenatally exposed to cineole associated with ethanol intoxication exhibited heightened responsiveness to the nutritive surrogate nipple when in the presence of the odor used as a CS during gestation (125). These results are depicted in Figure 2.…”
Section: Fetal Learning About Ethanol Derived From Maternal Intoxicatmentioning
confidence: 85%
“…This correlational study strongly suggested that physiologic changes in the prenatal milieu, derived from the state of ethanol intoxication, act as important components in modulating fetal ethanol learning processes (118,125,141,142). Although these results cannot address a causal relation between hypothermia as a US and fetal learning about ethanol's chemosensory cues, these results emphasize that analysis of early memories involving experiences with ethanol requires vigilant consideration of contingencies existing between ethanol's sensory properties and a variety of ethanol's physiologic consequences.…”
Section: Fetal Learning About Ethanol Derived From Maternal Intoxicatmentioning
confidence: 99%
See 1 more Smart Citation
“…The odor, taste and somatosensory stimulation provided by EtOH in the amniotic fluid is perceived by the fetus (Domínguez et al, 1996). The fetus can also experience EtOH's postabsorptive pharmacological effects (Domínguez et al, 1996; Abate et al, 2000), originating the opportunity for the development of an association between EtOH's chemosensory properties and its pharmacological effects (Abate et al, 2000, 2001, 2002). Additionally, it has been proposed that exposure to EtOH during early ontogeny involves learning about positive effects of the drug, since at this developmental stage rats seem more susceptible to EtOH's effects than later in life (Molina et al, 2007b; Pautassi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%